Perubahan Pengetahuan, Sikap, Praktek Diet dan Kadar Gula Darah Sesudah Konseling Gizi Pada Penderita Diabetes Melitus Rawat Inap di Rumah Sakit Umum Daerah Tabanan - Sukraniti, Desak Putu; Mataram, I Komang Agusjaya; Adistyanthi Dinar, I Gusti Ayu Agung Amanda (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Diabetes mellitus can be influenced by knowledge, attitudes, dietary practices and blood sugar levels. The purpose of the study was to determine changes in knowledge, attitudes, dietary practices and blood sugar levels after nutritional counseling in patients with Diabetes Mellitus hospitalized at Tabanan Regional General Hospital. This study used Pre experimental with One-Group Pretest-Posttest Design. The number of samples used was 30 patients with Diabetes Mellitus hospitalized at Tabanan Regional General Hospital. Data collection includes: age, education, gender, knowledge, attitude, dietary practices and blood sugar levels. Data were collected twice, before and after counseling. To determine whether there are changes in knowledge, attitudes, dietary practices and blood sugar levels before and after counseling, Wilcoxon test was used. The results showed a p-value of 0.000 on knowledge, attitudes and blood sugar levels before and after counseling which means there is a significant change and a p-value of 0.087 which means there is no significant change in dietary practices before and after counseling.